2006
DOI: 10.1161/01.res.0000247065.11756.19
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 4–Mediated Disruption of the Alveolar Septal Barrier

Abstract: Disruption of the alveolar septal barrier leads to acute lung injury, patchy alveolar flooding, and hypoxemia. Although calcium entry into endothelial cells is critical for loss of barrier integrity, the cation channels involved in this process have not been identified. We hypothesized that activation of the vanilloid transient receptor potential channel TRPV4 disrupts the alveolar septal barrier. Expression of TRPV4 was confirmed via immunohistochemistry in the alveolar septal wall in human, rat, and mouse lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
335
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(359 citation statements)
references
References 58 publications
21
335
2
1
Order By: Relevance
“…Another report (58) demonstrated that 4␣-PDD increased lung endothelial permeability, which was blocked by RR. The effect of TRPV4 on barrier functions observed in those reports contradicts that obtained in our own study.…”
Section: Discussionmentioning
confidence: 94%
“…Another report (58) demonstrated that 4␣-PDD increased lung endothelial permeability, which was blocked by RR. The effect of TRPV4 on barrier functions observed in those reports contradicts that obtained in our own study.…”
Section: Discussionmentioning
confidence: 94%
“…TRPC3-and TRPC6-induced Ca 2+ inflow underpin the stimulatory effect of VEGF on endothelial proliferation, migration and permeability [18,231,236] , while ATP exploits TRPC3 to activate NF-κB and increase vascular cell adhesion molecule-1 expression [237] . TRPC3-driven NO synthesis and vasore- TRPV1 TRPV2 TRPV3 TRPV4 TRPV5 TRPV6 PCa/PNa and conductance (pS) [202] 10, 35-80 1-3, NM 12, 172 6, 90 > 100, 75 > 100, 40-70 Human coronary artery ECs [300] (+RT-PCR, WB, IHC) Human pulmonary artery ECs [415] +(RT-PCR) +(RT-PCR) +(RT-PCR) Human pulmonary microvascular ECs +(RT-PCR) Human cerebral microvascular ECs [272] +(RT-PCR, IC) Human cerebral arterioles ECs [305] +(RT-PCR, IHC) Human dermal microvascular ECs [319] +(RT-PCR, WB) Breast cancer derived microvascular ECs [319] +(RT-PCR, WB) Human umbilical vein ECs [227,277,296,301] +(RT-PCR) +(WB, IHC) Mouse aortic ECs [280,285,299,306] +(WB) +(RT-PCR, WB, NM, IHC) Mouse pulmonary artery ECs [313] +(WB, IHC) Mouse mesenteric artery ECs [27,280,302] +(RT-PCR, WB, IC) +(RT-PCR, IC) Mouse cerebral microvascular ECs +(RT-PCR) +(RT-PCR, WB) +(RT-PCR) Mouse dermal microvascular ECs [307] +(RT-PCR, WB) Mouse carotid artery ECs [290,296] +(IHC) Rat mesenteric artery ECs [226,275,302] +(WB) +(WB, IC, IHC) Rat femoral artery ECs [312] +(RT-PCR, IC) Rat pulmonary artery ECs [303] +(WB, IHC) Rat renal artery ECs [303] +(IHC) Rat cardiac microvascular ECs [303,…”
Section: A Drop In Luminal Camentioning
confidence: 99%
“…TRPV1 activity has been related to different aspects of chronic respiratory disease such as neurogenic inflammation (15,16), irritant-induced chronic cough (13,14), and airway hypersensitivity (17). TRPV4 activation disrupts alveolar barrier in animal models (18) and has been associated with chronic obstructive pulmonary disease in humans (19). Together, these evidences make TRPV1 and TRPV4 interesting candidate genes for asthma.…”
Section: Trpv1mentioning
confidence: 99%